Landslide susceptibility zone in steep slope landscape at Gunung Kidul Regency, southeast part of Yogyakarta, Indonesia - Saenkang, Phoulid (2022)
Gunung Kidul is located in Central Java Province, Indonesia. which is vulnerable to geological hazard such as floods and earthquake. However, it is also susceptible to landslide in some areas of Gunung Kidul which contributes to damage and loss. The study area is covers sub districts such as: Patuk, Gedangsari, Nglipar, Ngawen, Playen. It covers an area of 1,485.36 km2 and had a population of 747,161 at the 2020 Census. This research aims to produce a landslide susceptibility map, construct the detailed geological map, consider geomorphology aspect, lithology aspect, soil-rock masses, hydrogeology/groundwater aspect, structural geology aspect, land use. The parameters that caused the occurrence of landslide were determined and the landslide susceptibility map was produced using Weightage Overlay Method (WOM) in ArcGIS software. Results showed that the susceptibility map was classified into three zones which is low, moderate and high zone. The factor that triggered the landslide were identified which is heavy rainfall intensity and earthquake. As a conclusion, the ability to detect landslide susceptibility led to a better understanding of landslide mechanisms for the research area, thus leading to an enhanced identification of the most likely failure sites within a landslide-prone area. © Published under licence by IOP Publishing Ltd.